PEMANFAATAN INFORMASI SPASIAL BERBASIS SIG UNTUK PEMETAAN TINGKAT KERAWANAN LONGSOR DI KECAMATAN SUMALATA - Akbar, La Ode Juni; Zees, Dewi Sartika T.; Djau, Bambang (Universitas Bina Taruna Gorontalo, 2024)
Abstract: The utilization of GIS-Based Spatial Information for Mapping the Landslide Vulnerability Levels in Sumalata District Sumalata district is an area with hilly topography which is dominated by relatively steep slopes. The landslide disaster frequently occurs in this study setting. This study aims to explore the utilization of GIS-Based Spatial Information for mapping the landslide vulnerability levels in Sumalata District. Based on the observation on March to April 2024, there are 7 landslide disaster occurred. However, the disaster can be minimized by mapping the landslide-prone area. The approach used in this study is a land unit approach. The classification of land unit is obtained from the overlay of thematic map which consist of maps of rainfall, land cover, slopes, rocks and soil type maps. The result of this study shows that the classification of the landslide vulnerability categorized in three aspects, there are low grade with 49,304 Ha, medium grade with 13.409,71 Ha, and high grade with 16.921,36 Ha.